2019
DOI: 10.3390/jcm8060815
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid and Fibroblast Growth Factor 19 Regulation in Obese Diabetics, and Non-Alcoholic Fatty Liver Disease after Sleeve Gastrectomy

Abstract: Background: Sleeve gastrectomy (SG) is an effective treatment for obesity and type 2 diabetes mellitus (T2DM), and non-alcoholic fatty liver disease (NAFLD); however, the mechanism is not completely understood. Bile acids and fibroblast growth factors (FGFs) are involved in the regulation of energy metabolism. Methods: We investigated the roles of total bile acid and FGF 19 in T2DM remission and NAFLD improvement in obese subjects undergoing SG. A total of 18 patients with obesity and T2DM undergoing laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Following SG, data are less consistent. Some researchers showed increased [13,29,30] or decreased [31] levels, whereas others showed transiently decreased [40] or unchanged [17,32,33] levels at different time points after surgery associated, or not, with metabolic improvements (Table 3). Still, the question arises if there is an acute change at one week and one month after surgery and if this change is related or not to the improvement of IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following SG, data are less consistent. Some researchers showed increased [13,29,30] or decreased [31] levels, whereas others showed transiently decreased [40] or unchanged [17,32,33] levels at different time points after surgery associated, or not, with metabolic improvements (Table 3). Still, the question arises if there is an acute change at one week and one month after surgery and if this change is related or not to the improvement of IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, while circulating BAs have been demonstrated to increase following RYGB [13,18,[26][27][28], the effect of SG on BA has shown mixed results. Namely, some authors reported increased concentrations [13,29,30], others decreased [31] circulating levels of BA, and finally, others detected no change after SG [32,33]. Most importantly, the exact timing of the BA changes and their potential role in the reduction of IR and restauration of insulin sensitivity are not fully elucidated [3,11,34].…”
Section: Introductionmentioning
confidence: 99%
“…Our SG procedure was performed using 4-0 nonabsorbable silk sutures and according to the method of Al-Sabah et al [10]. Overall, the SG procedure resulted in the resection of the greater curvature from the distal antrum (approximately 0.5 cm proximal to the pylorus) until the angle of His, resecting the fundus completely [11,12].…”
Section: Sgp Procedurementioning
confidence: 99%
“…The interaction between human ACE2 and SARS-CoV-2 is a reasonable but partial explanation of the mechanism of gastrointestinal and hepatic manifestations. Gut hormones 12 14 and hepatokines such as bile acid and fibroblast growth factor, 15 which regulate appetite, nutrient absorption, and immunometabolism, may deserve further exploration. Further investigations are needed for elucidation of the comprehensive pathophysiology and possible treatments of COVID-19.…”
mentioning
confidence: 99%